I Dream of a Needle / Articulate, Please / When the Screen Retracts - Sample, Susan (Ars Medica, 2025)
The attached three poems focus on existential and emotional consequences of medical practices from professional and personal perspectives. In "I Dream of a Needle," I write as a daughter watching my father undergo a bone marrow biopsy while the oncologist assures me the procedure doesn't cause pain. In "Articulate, Please," I write as a medical school faculty member responding to a student traumatized during her first time "pronouncing" a patient. In the final poem, "When the Screen Retracts," I write as a member of a healthcare team participating in a remembrance ceremony to help families and caregivers of recently deceased patients heal. For nine years, I've worked as the writer-in-residence at a comprehensive cancer center, guiding patients and family as they make sense of ther cancer experiences. The remembrance ceremony stood out as an occasion where I could help all of us find words to express an inexpressible aspect of patient care.